RUANG INTERAKTIF DI MERUYA UTARA - Ursula Andrea (Jurusan Arsitektur dan Perencanaan, 2020)
Third place is a neutral place, and simple (unpretentious). This place must be playful or fun for anyone, so that when leaving the third place, people come out happily. This place has no rules at home or work. Third place is also a place where people gather, and have the same status. Also in this project the third place comes as a form of open architecture that is friendly to the environment and makes the city better. The main activity of this project is the interaction with the programs offered, the activity itself and with fellow visitors. The focus of the third place is shown on the impact of